Development of a Subcutaneous Fixed‐Dose Combination of Pertuzumab and Trastuzumab: Results From the Phase Ib Dose‐Finding Study. (19th December 2018) - Kirschbrown, Whitney P.; Wynne, Chris; Kågedal, Matts; Wada, Russ; Li, Hanbin; Wang, Bei; Nijem, Ihsan; Badovinac Crnjevic, Tanja; Gasser, Helena; Heeson, Sarah; Eng‐Wong, Jennifer; Garg, Amit
Abstract: Adding pertuzumab to trastuzumab (both monoclonal antibodies targeting human epidermal growth factor receptor 2 [HER2]) has proven survival benefits when combined with chemotherapy for patients with HER2‐positive breast cancer. The combination of pertuzumab and trastuzumab together in 1 vial for subcutaneous (SC) administration is being developed as a ready‐to‐use formulation to reduce the treatment burden on patients while improving healthcare efficiency. An open‐label, 2‐part, phase Ib dose‐finding study (NCT02738970) was undertaken in healthy male volunteers (part 1) and female patients with HER2‐postive early breast cancer who had completed standard (neo)adjuvant treatment (part 2). This study aimed to identify an SC pertuzumab dose given with recombinant human hyaluronidase that results in comparable exposure to that of the intravenous (IV) pertuzumab dose, based on pertuzumab serum trough concentration and area under the serum concentration–time curve. Pharmacokinetics (PK), safety, and tolerability of a single dose of SC pertuzumab given alone or in a fixed‐dose combination (comixed or coformulated) with trastuzumab were also assessed. A maintenance dose of 600 mg for SC pertuzumab resulted in an equivalent exposure to that of IV pertuzumab, and no new safety signals were identified for SC pertuzumab or trastuzumab. A loading dose of 1200 mg for SC pertuzumab was selected based on approximate dose proportionality. The PK and safety results support further development of a fixed‐dose coformulation combination of pertuzumab and trastuzumab for SC administration, which will be investigated in an upcoming phase III trial in patients with HER2‐positive early breast cancer.